A giant atrial septal aneurysm causing tricuspid valvular obstruction. Issue 8 (13th January 2020) - Lin, Shan; Li, Yuman; Xu, Lingling; Lin, Ling; Yang, Yali; Xie, Mingxing
Abstract: Atrial septal aneurysm (ASA) is a rare congenital malformation consisting of redundant atrial septal tissue that bulges into either the right or the left atrium. Here, we report the case of a 45‐year‐old man with a giant ASA prolapsing into the tricuspid orifice and leading to tricuspid valvular obstruction. He was treated successfully by resection of the ASA and repair of the resulting atrial septal defect. Our case indicates the utility of transthoracic, contrast, and transesophageal echocardiography to characterize a huge ASA causing tricuspid valvular obstruction.